DEKOMPOSISI AIR-METANOL MENJADI HIDROGEN PADA SEMIKONDUKTOR NATRIUM TANTALUM OKSIDA DENGAN MENGGUNAKAN LANTANUM SEBAGAI DOPING - Husni Husin, Komala Pontas, Hesti Meilina, Fikri Hasfita (Jurnal Teknik Kimia USU, 2013)
Synthesis of semiconductor photocatalysts lanthanum-doped sodium tantalum oxide (La-NaTaO3) and its performance on water-methanol decomposition has been carried out. This research aimed is to examine the effect of methanol as an electron donor in the reaction to photocatalytic of hydrogen production. The samples are characterized by x-ray diffractometer (XRD) to determine its composition. The results indicate that the products are composed of NaTaO3 and Ta2O5. The reaction is conducted by irradiating of water-methanol of 400 ml and 1 g of photocatalyst in Pyrex glass reactor for 4 h at a temperature of 30 oC.The methanol solution is poured into the reactor of 5, 10, and 15 vol.%.  For comparison, in this reaction is also used only pure water. The results depict that the rate of photocatalytic hydrogen evolution from pure water as much as  0.3(mmol / g.h). Hydrogen generation rate increased significantly when the methanol are added of 5%, 10%, and 15%, ie. 2.68, 4.79 and 8.72 ,(mmol / g.h),  respectively. This has been attributed to the effect of added methanol, which acts as sacrificial electron donor and consumes photogenerated holes and/or oxygen, thereby decreasing the rates of electron-hole recombination. Reaction mechanism in semiconductor particles of NaTaO3 is also reported.